2014
DOI: 10.1111/azo.12068
|View full text |Cite
|
Sign up to set email alerts
|

Confocal imaging and phylogenetic considerations of the subcutaneous neurons in the Atlantic hagfish Myxine glutinosa

Abstract: Zaccone, G., Fudge, D.S., Winegard, T.M., Capillo, G., Kuciel, M., Funakoshi, K. and Lauriano, E.R. 2015. Confocal imaging and phylogenetic considerations of the subcutaneous neurons in the Atlantic hagfish Myxine glutinosa. -Acta Zoologica (Stockholm) 96: 209-217.We used confocal microscopy and immunohistochemistry to characterize the morphology of the subcutaneous neurons and the innervation of the slime glands and striated muscles in the hagfish Myxine glutinosa. A rich plexus of 5HT-, ChAT-and TH-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
1
12
1
Order By: Relevance
“…The presence of myoepithelial cells in the S. canicula rectal gland secretion has been challenged (Shuttleworth, 1988), because the glands of S. canicula did not respond to VIP (Anderson et al, 1995;Thorndyke & Shuttleworth, 1985). But in the present study has been demonstrated numerous nerve fibers both of the capsule that of the parenchyma of the rectal gland peptide (VIP) and substance P positive; furthermore nNOS immunoreactivity in nerve fibers of the gland capsular wall and nerve varicosities in close proximity to the secretory cells, show that these substances are expressed by nerves close glandular parenchyma and the nerve fibers directly innervate the secretory epithelium (Zaccone et al, 2015a(Zaccone et al, , 2015b. Already, Chan and Phillips (1967) described argentaffin cells in lip-shark Hemiscyllium plagiosum rectal gland, we detected VIP and substance P immunoreactive cells (neuroendocrine like cell) in the glandular parenchyma between secretary cells.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The presence of myoepithelial cells in the S. canicula rectal gland secretion has been challenged (Shuttleworth, 1988), because the glands of S. canicula did not respond to VIP (Anderson et al, 1995;Thorndyke & Shuttleworth, 1985). But in the present study has been demonstrated numerous nerve fibers both of the capsule that of the parenchyma of the rectal gland peptide (VIP) and substance P positive; furthermore nNOS immunoreactivity in nerve fibers of the gland capsular wall and nerve varicosities in close proximity to the secretory cells, show that these substances are expressed by nerves close glandular parenchyma and the nerve fibers directly innervate the secretory epithelium (Zaccone et al, 2015a(Zaccone et al, , 2015b. Already, Chan and Phillips (1967) described argentaffin cells in lip-shark Hemiscyllium plagiosum rectal gland, we detected VIP and substance P immunoreactive cells (neuroendocrine like cell) in the glandular parenchyma between secretary cells.…”
Section: Discussioncontrasting
confidence: 49%
“…Smooth muscle cells in the layer are continuous with the smooth muscle that forms a sphincter around the gland. In a previous study has been used this antibody to mark smooth muscle cells in the connective tissue of the hagfish Myxine glutinosa slime gland capsule (Zaccone et al, ). Also, this antibody has been used as a marker to demonstrate the presence of myoepithelial cells in the gland central duct.…”
Section: Discussionmentioning
confidence: 99%
“…A Zeiss LSM DUO confocal laser scanning microscope with a META module (Carl Zeiss MicroImaging GmbH, Jena, Germany) equipped with an argon laser (458, 488 l) and two helium–neon lasers was used to examine sections and take images (543 and 633 l) [ 33 ]. All the images were digitalized into a 2048 by 2048 pixel array at an 8-bit resolution.…”
Section: Methodsmentioning
confidence: 99%
“…Techniques for immunolabelling were similar to those previously described for adult fish visceral organ tissues (Zaccone et al . , ). Details of antibodies used in this study are summarized in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Nerve fibres and bundles were also identified using antibodies to calbindin that is a general neuronal marker, and its labelling of neural structures in various fish species has been previously characterized (Zaccone et al . , ; Kuciel et al . ).…”
Section: Methodsmentioning
confidence: 99%